Kronično funkcionalno zaprtje otrok - Orel, Rok (Medicinski razgledi, 1996)
Cronic constipation is a common problem in children. The paper presents organic causes of constipation and the major risk factors for constipation, which are to be considered in the absence of evident organic causes. Good knowledge of normal rhythm and frequency of bowel movements appropriate for the child's age is a prerequisite for correct diagnosis of cronic constipation. The disorder is frequently associated with encopresis and anal bleeding. The principal diagnostic aproach to constipation is presented, as well as the main aspects of proper therapy, which should include the following: fiber-rich diet, counselling, training in bowel routine, medication and the use of bio feedback technique.
Keywords: medicina; medicine; otrok; zaprtje; otroške bolezni